2011
DOI: 10.1111/j.1470-6431.2010.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Online shopping among Chinese consumers: an exploratory investigation of demographics and value orientation

Abstract: The current study examined the relationship between Chinese consumers' personal value orientations and their Internet usage and online shopping behaviour. The study was based on responses from a sample of 1620 respondents in five cities in China. Based on Schwartz's value structure, four value orientations were identified and named as ‘openness to change orientation’, ‘self‐enhancement orientation’, ‘conservation orientation’ and ‘self‐transcendence orientation.’ Logistic regression analysis was used to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…The other bipolar dimensions, the Openness to change and Conservation dimensions, are useful to explain the adoption of new channel shopping or new styles. Wu et al (2011) found that a person who has a stronger Openness to change orientation is more likely to use the internet in everyday life and to feel the internet is convenient to purchase products online, indicating that the Openness to change orientation facilitates adopting new technology. Wang et al (2008) addressed that stimulation needs (i.e., a core value of Openness to change) are satisfied with new products, indicating a positive association between stimulation and consumer innovativeness.…”
Section: Schwartz Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other bipolar dimensions, the Openness to change and Conservation dimensions, are useful to explain the adoption of new channel shopping or new styles. Wu et al (2011) found that a person who has a stronger Openness to change orientation is more likely to use the internet in everyday life and to feel the internet is convenient to purchase products online, indicating that the Openness to change orientation facilitates adopting new technology. Wang et al (2008) addressed that stimulation needs (i.e., a core value of Openness to change) are satisfied with new products, indicating a positive association between stimulation and consumer innovativeness.…”
Section: Schwartz Valuesmentioning
confidence: 99%
“…Wu et al . () found that a person who has a stronger Openness to change orientation is more likely to use the internet in everyday life and to feel the internet is convenient to purchase products online, indicating that the Openness to change orientation facilitates adopting new technology. Wang et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…While research has found that these Chinese traditional cultural values influence various consumer behaviours, such as customer satisfaction (Yau, 1994), online shopping (Wu et al, 2011), thrift and spending (Lin et al, 2013), purchase decisions (Liang and He, 2012) and gift giving (Yau et al, 1999;Joy, 2001;Qian et al, 2007), there is little research as to the effect of these values on materialism and desire for luxury products. While research has found that these Chinese traditional cultural values influence various consumer behaviours, such as customer satisfaction (Yau, 1994), online shopping (Wu et al, 2011), thrift and spending (Lin et al, 2013), purchase decisions (Liang and He, 2012) and gift giving (Yau et al, 1999;Joy, 2001;Qian et al, 2007), there is little research as to the effect of these values on materialism and desire for luxury products.…”
Section: Introductionmentioning
confidence: 99%
“…The history and development of China has meant that there are strong traditional cultural values (face, harmony, guanxi) co-existing with two opposing political ideologies (Maoism and Deng's theory), even in a one-party state. While research has found that these Chinese traditional cultural values influence various consumer behaviours, such as customer satisfaction (Yau, 1994), online shopping (Wu et al, 2011), thrift and spending (Lin et al, 2013), purchase decisions (Liang and He, 2012) and gift giving (Yau et al, 1999;Joy, 2001;Qian et al, 2007), there is little research as to the effect of these values on materialism and desire for luxury products.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cognitive involvement infl uences perceived usefulness and perceived ease of use in all countries, but the relationship between affective involvement and behavioral intention does not hold in Germany (Smith et al 2013 ). Based on a sample of Chinese consumers, "Openness to change orientation" and "self-enhancement orientation" are found to have positive effects on respondents' online shopping behavior (Wu et al 2011 ). A study conducted in Israel fi nds that online shoppers are experienced internet users who valued online information searching.…”
Section: Consumer Behavior In Online Shoppingmentioning
confidence: 98%